A new Keggin-like niobium-phosphate cluster that reacts reversibly with hydrogen peroxide1. Issue 64 (18th August 2015) - Son, Jung-Ho; Casey, William H.
<x xml:space="preserve">Abstract</x> Solid niobium phosphate (NbOPO4·xH2O) is well known as a biomass-conversion catalyst, yet the chemical pathways are unclear. Here we report solution chemistry of a new niobophosphate cluster [H3Nb9P5O41]9− that reacts with H2O2 to form peroxo-Nb4P2, and this reaction can be reversed by hydrothermal treatment. We suggest that this cluster is a useful molecular model for the solid.